A robust study of the transmission dynamics of malaria through non-local and non-singular kernel - Jan, Rashid; Alyobi, Sultan; İnç, Mustafa; Alshomrani, Ali Saleh; Farooq, Muhammad (Amer Inst Mathematical Sciences-Aims, 2023)
It is valuable to measure the epidemiological significance of malaria, since there has been a growing interest in reducing malaria through improved local and national health care systems. We formulate the dynamics of malaria infection via a fractional framework to understand the intricate transmission route of malaria and to identify the role of memory for the control of malaria. The model is investigated for basic results, moreover, the basic reproduction number is determined symbolized by R0. We have shown the local stability of the disease-free steady-state of the system for for R0 < 1. The existence and uniqueness of the solution of the system are examined. The Adams Bashforth approach in fractional form is applied to analyse the numerical outcomes of the mathematical model. Furthermore, in order to realise more efficiently, the Atangana-Baleanu (ABC) fractional nonlocal operator, which was just invented, is used. The stability of the system is investigated through the fixed-point theorems of Krasnoselskii and Banach. The behaviour of the approximation solution is illustrated in terms of graphs across various fractional values and other factors of the systems. After all, a brief analysis of the simulation's findings is provided to explain how infection transmission dynamics occur in society.
Keywords: malaria; fractional derivatives; mathematical model; quantitative analysis; dynamical behaviour